The Effect of Accountability, Work–Life Balance, and Independence on Audit Quality at Public Accounting Firms (KAP) in Pekanbaru - Zahra Darmayati Ginting, Siti; Ramashar, Wira (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2025)
Audit reports are an important part of the company, so the quality of good audit results must be maintained. To maintain audit quality, an auditor who has accountability, work life balance and independence is needed. Therefore, the purpose of this study is to examine the direct relationship between accountability, work life balance and independence in relation to audit quality, especially KAP in Pekanbaru City. The research methodology used in this study used a quantitative approach with primary data types obtained through distributing questionnaires. In this study used saturated sampling techniques with a total sample of 47 people. In addition, SPSS version 26 is used as a data analysis tool. Based on the results of hypothesis testing with a significance level of 5% it is known that accountability, work life balance and independence have a positive effect on audit quality at KAP Pekanbaru. In general, the three dependent variables have a positive effect on audit quality at KAP Pekanbaru.